Cardiac Adrenoceptors: Physiological and Pathophysiological Relevance - Otto-Erich Brodde; Heike Bruck; Kirsten Leineweber (Elsevier, 2006)
Abstract.: At present, nine adrenoceptor (AR) subtypes have been identified: α1A-, α1B-, α1D-, α2A-, α2B-, α2C-, β1-, β2-, and β3AR. In the human heart, β1- and β2AR are the most powerful physiologic mechanism to acutely increase cardiac performance. Changes in βAR play an important role in chronic heart failure (CHF). Thus, due to increased sympathetic activity in CHF, βAR are chronically (over)stimulated, and that results in β1AR desensitization and alterations of down-stream mechanisms. However, several questions remain open: What is the role of β2AR in CHF? What is the role of increases in cardiac Gi-protein in CHF? Do increases in G-protein-coupled receptor kinase (GRK)s play a role in CHF? Does βAR-blocker treatment cause its beneficial effects in CHF, at least partly, by reducing GRK-activity? In this review these aspects of cardiac AR pharmacology in CHF are discussed. In addition, new insights into the functional importance of β1- and β2AR gene polymorphisms are discussed. At present it seems that for cardiovascular diseases, βAR polymorphisms do not play a role as disease-causing genes; however, they might be risk factors, might modify disease, and/or might influence progression of disease. Furthermore, βAR polymorphisms might influence drug responses. Thus, evidence has accumulated that a β1AR polymorphism (the Arg389Gly β1AR) may affect the response to βAR-blocker treatment. Keywords:: heart failure, cardiac β1- and β2-adrenoceptors, β-adrenoceptor polymorphism, cardiac G-protein, G-protein-coupled receptor kinase